Síntese e investigação da atividade biológica de pirazóis funcionalizados - Tavares, Luciana de Carvalho (2006)
In this work, a method for the synthesis of a series of heterocyclic compounds that preserve the amino group of the starting material, is presented. For this study, a-oxoketene O,N-acetals were obtained from the reaction of b-oxothioxo ester and different primary amines. The reactivity of the elctrophilic centers of O,N-acetals was investigated through cyclization reactions using 1,2-dinucleophiles such as hydrazine and phenylhydrazine with the reaction carried out in solid support. The functionalized heterocycles 5(3)-amino substituted 3(5)-phenyl 1H-pyrazoles and 3-amino substituted 1,5-diphenyl pyrazoles, were obtained selectively. When 1,2-dinucleophiles such as hydrazine and phenylhydrazine hydrochloride were used, ethoxy pyrazoles 5(3)-ethoxy 1H-pyrazole, 3-ethoxy 1,5-diphenyl pyrazole and 5- ethoxy 1,3-diphenyl pyrazole, were obtained, demonstrating the influence of these salts in the formation of different substitution pattern. The investigation of the possible biological activity of the pyrazoles systems obtained was performed in vitro and was accomplished through the analysis of the antimicrobial activity by the Bioautography method and Minimal Inhibitory Concentration (MIC) front to a collection of different indicative microorganisms. The inhibitory activity of the acetylcholinesterase (AChE) enzyme was also investigated.